Toponyms of the Tambopata River Basin (Puno) Felipe Huayhua Pari Dpto. Acad. de Lingüística CILA-FLCH-UNMSM fhuayhua@gmail.com Resumen En este artículo presentamos los topónimos de la cuenca del río Tambopata en la región de Puno. Constituye solo una pa - Huayhua Pari, Felipe (2018)
In this article we present the place names of the Tambopata river basin in the Puno region. It constitutes only part of the broader study that we have carried out on the lexicon of place names, plants, animals, diseases and objects collected in the Tambopata river basin, which includes three districts in the province of Sandia: Yanahuaya, San Juan del oro and Putina in the province of Sandia. We analize linguistically – phonologically, lexically and semantically – the variation of the names related to the local language. BesideThe theory of dialectal variation, the method of linguistic geography or geolinguistics are applied to lift isoglosas with descriptive and interpretative focus, inspired in descriptive and functional linguistics. The hypothesis set up has been proven that the language and culture has being abandoned slowly. The aim of this study was to prove the dialectization of Aymara language, denotation and connotation patterns. This study will help the elaboration of linguistic cathegories, regional linguistic dictionaries. As well it will contribute to the knowledge of Andean wisdom that are current in the culture, and will veriforce the interculturality.